Typological Characteristics of Translation of Romantic French Prose on the basis of Antoine de Saint-Exupery’s work «The Little Prince». (Eurasian Journal of Philology Science and Education, 2015)
The article «Typological Characteristics of Translation of Romantic French Prose on the basis of Antoine de Saint-Exupery’s work «The Little Prince» carries out the comparative analysis of the original text and its translation made by Nora Gal’ and G. Velle; it also deals with the assessment of the level of adequacy and equivalence, preservation of the author’s outlook and axiological criteria. Particular attention is paid to preservation of historical and literary context, symbolism of images and typologicalconstituent in translation. The life and creative activity of Antoine de Saint-Exupery is deeply connected with historical and social realities of the early XX century. Reconstructing the vertical context, the identification of factors, which influenced the formation of the author’s method, the designation of the writer’s value parameters and revealing his thesaurus are conceptually important for the implementation of full-scale comparative analysis of translation. In order to carry out the comparative analysis of Saint-Exupery’s work the methods of synchronization and search were used. It should be noted that the works devoted to the translation of A. Saint-Exupery’s book, his creative activity analysis and the study of his writings are very few. For this reason the topic of the article is relevant today.
Keywords: typology; vertical context; outlook parameters; axiological characteristics; equivalent; adequacy; symbol; characters typology